2023
DOI: 10.1021/acsami.3c01749
|View full text |Cite
|
Sign up to set email alerts
|

Two Bulk-Heterojunctions Made of Blended Hybrid Nanocomposites for High-Performance Broadband, Self-Driven Photodetectors

Abstract: Heterojunctions based on low dimensional semiconducting materials are one of the most promising alternatives for next-generation optoelectronic devices. By choosing different dopants in high-quality semiconducting nanomaterials, p-n junctions can be realized with tailored energy band alignments. Also, p-n bulkheterojunctions (BHJs) based photodetectors have shown high detectivity because of the suppressed dark current and high photocurrent, which are due to the larger built-in electric potential within the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…2(d), the MoS x Se 2− x nanosheet presents four additional peaks at 161.52, 162.92, 164.12 and 167.32 eV attributed to Se 3p 3/2 , S 2p 1/2 , S 2p 3/2 and Se 3p 1/2 , respectively, which may indicate possible overlaps contributing to S 2− and Se. 2–45 The S 2s peak was also observed at the core of 227.12 eV. Moreover, the XPS spectra of the MoS 2 are shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…2(d), the MoS x Se 2− x nanosheet presents four additional peaks at 161.52, 162.92, 164.12 and 167.32 eV attributed to Se 3p 3/2 , S 2p 1/2 , S 2p 3/2 and Se 3p 1/2 , respectively, which may indicate possible overlaps contributing to S 2− and Se. 2–45 The S 2s peak was also observed at the core of 227.12 eV. Moreover, the XPS spectra of the MoS 2 are shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The ability of PDs to achieve self-driven detection is largely attributed to this unique structural feature. 23,24 Additionally, the research team also developed a variety of strategies for enhancing the performance of optoelectronic devices, such as software simulation 25 and a suppressed surface. 26 A V 2 O 5 /rGO hybrid PD was prepared by a hydrothermal method achieving good performance due to the carrier generation mechanisms increasing the responsivity and detectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The R can be defined as the ratio of photocurrent to the intensity of illumination power, and it is expressed asR=IphotoPill$$R = \frac{I_{\text{photo}}}{P_{\text{ill}}}$$Where Pill$P_{\text{ill}}$ is the intensity of the illumination. [ 15,44 ] The responsivity of the device was measured for different wavelengths, i.e., 405, 532, 1,050, and 1,550 nm which is given in Figure 4 a. It was found that the value of the responsivity for the 405 nm wavelength is 96 mA W −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The improved understanding of the physics and chemistry of the transport mechanisms in perovskites has led to rapid enhancement of the device performances with striking progress. 1–11 Traditional photodetectors that convert optical signals to electrical signals are primarily based on InGaAs, GaN, and Si that require elaborate film growth techniques. 12–21 More recently solution processible semiconductor-based hybrid perovskites and organic polymers have shown promise in applications like optical communications, imaging, chemical and biological sensing.…”
Section: Introductionmentioning
confidence: 99%